Anonymous body or first patient? A status report and needs assessment regarding the personalization of donors in dissection courses in German, Austrian, and Swiss Medical Schools. Issue 3 (14th October 2017) - Hasselblatt, Friederike; Messerer, David A.C.; Keis, Oliver; Böckers, Tobias M.; Böckers, Anja
Abstract : Many Anglo‐American universities have undertaken a paradigm shift in how the dissection of human material is approached, such that students are encouraged to learn about the lives of body donors, and to respectfully "personalize" them as human beings, rather than treating the specimens as anonymous cadavers. For the purposes of this study, this provision of limited personal information regarding the life of a body donor will be referred to as "personalization" of body donors. At this time, it is unknown whether this paradigm shift in the personalization of body donors can be translated into the German‐speaking world. A shift from donor anonymity to donor personalization could strengthen students' perception of the donor as a "first patient, " and thereby reinforce their ability to empathize with their future patients. Therefore, this study aimed to collect data about the current status of donation practices at German‐speaking anatomy departments ( n = 44) and to describe the opinions of anatomy departments, students ( n = 366), and donors ( n = 227) about possible donor personalization in medical education. Anatomy departments in Germany, Austria, and Switzerland were invited to participate in an online questionnaire. One‐tenth of registered donors at Ulm University were randomly selected and received a questionnaire (20 items, yes‐no questions) by mail. Students at the University of Ulm were also surveyed at the end of the dissection course (31 items, six‐point Likert‐scale). The majority of students were interested in receiving additional information about their donors (78.1%). A majority of donors also supported the anonymous disclosure of information about their medical history (92.5%). However, this information is only available in about 28% of the departments surveyed and is communicated to the students only irregularly. Overall, 78% of anatomy departments were not in favor of undertaking donor personalization. The results appear to reflect traditional attitudes among anatomy departments. However, since students clearly preferred receiving additional donor information, and most donors expressed a willingness to provide this information, one could argue that a change in attitudes is necessary. To do so, official recommendations for a limited, anonymous personalization of donated cadaveric specimens might be necessary. Anat Sci Educ 11: 282–293. © 2017 American Association of Anatomists.